2‐(Pyridinium‐1‐yl)‐1, 1‐bis(perfluoroalkylsulfonyl)ethan‐1‐ide: A Practical Reagent for Synthesis of Strongly Acidic 1, 1‐Bis(perfluoroalkylsulfonyl)alkanes. Issue 34 (18th April 2017) - Yanai, Hikaru; Takahashi, Ryuta; Takahashi, Yoichi; Kotani, Akira; Hakamata, Hideki; Matsumoto, Takashi
Abstract: On mixing (Rf SO2 )2 CH2 (Rf =perfluoroalkyl), paraformaldehyde, and substituted pyridines, a three‐component reaction proceeded smoothly to give unusual zwitterions bearing both pyridinium and stabilized carbanion moieties in good to excellent yields. Of these, 2‐fluoropyridinium derivatives rapidly dissociated in acetonitrile to give equilibrium mixtures of the zwitterions and (Rf SO2 )2 C=CH2 /2‐fluoropyridine, as confirmed by detailed variable‐temperature NMR studies. The dynamic behavior of such 2‐fluoropyridinium compounds allows them to be used as shelf‐stable, easy‐to‐handle sources of (Rf SO2 )2 C=CH2 . With these reagents, strongly acidic carbon acids (Rf SO2 )2 CHR were synthesized, which served as a new type of acid catalysts. Moreover, C−C bond‐forming reactions with a ketene silyl acetal proceeded efficiently with Tf2 C=CH2 generated in situ. Abstract : Dropping acid : 2‐Fluoropyridinium compounds, which were prepared from (Rf SO2 )2 CH2 (Rf =perfluoroalkyl), paraformaldehyde, and 2‐fluoropyridine, were developed as shelf‐stable, easy‐to‐handle sources of (Rf SO2 )2 C=CH2 (see scheme). By reaction of several nucleophiles with such reagents, superacidic carbon acids (Rf SO2 )2 CHR were successfully synthesized.